Redesigning Sciences Courses based on A Local Senior High School in Iloilo, Philippines’ Student Performances and Perspectives towards Hybrid Learning Approach - Donna Hembra Gabor; Leona Marie Canaway Camano (Journal of Science Learning, 2023)
This study aimed to examine learners' perspectives on the hybrid learning approach, using printed modules and social media as learning materials to redesign science courses and improve their performances. This study involved 37 students from Tacuyong Sur National High School, 20 from the Grade 9 class and 17 from the Grade 12 Technical Vocational Livelihood (TVL) class in the fourth quarter of the school year 2021-2022. The 5-items multiple-choice test assesses student performance. A survey question determined learners' perspectives on hybrid learning after revising the delivery mode for science courses. Student performances based on their pre-test/post-test revealed the benefits and problems connected with the hybrid learning approach. Program for statistical analysis of sampled data (PSPP) interpreted the survey and student performance. Hybrid learning survey results revealed a practical approach to improve science learners' performances during the COVID-19 pandemic. Data results through teacher-technology innovation demonstrated the effectiveness of hybrid learning techniques to help teachers and curriculum planners redesign course subjects that improve science student performances.